Public Relations Marketing Strategy in the Unissula New Student Admission Program - Fikri Shofin Mubarok; Trimanah Trimanah; Olivia Fachrunnisa (Universitas Islam Sultan Agung, 2025)
The main source of income for Private Universities (PTS) is from payments received from students. Therefore, PTS must be more creative in attracting new students. Unissula is a private university in Central Java with the highest number of students during the 2023 New Student Admissions (PMB) period, reaching 7346. This figure far exceeds the target of 5698. Unissula's Marketing and Public Relations (PH) UPT is a unit mandated by the Rektor to be responsible for the overall PMB program. In practice, UPT PH synergizes with all leaders at the university level, faculties, study programs and other units. This research aims to describe the synergy of UPT PH with all internal stakeholders in achieving PMB targets. This research uses a qualitative case study approach. The data collection technique was carried out using in-depth interviews with 3 informants determined by purposive sampling and observation at PMB meetings. Data analysis techniques are carried out through data reduction, data presentation and drawing conclusions. The research results show that there is a strategic policy from the Rektor which is the driving force for the implementation of three marketing public relations strategies, namely pull strategy, push strategy and pass strategy. The results of this research can contribute to other private universities which are experiencing a decrease in the number of students or who want to increase the number of students